Kontribusi Parental Beliefs dan Self-Regulated Learning terhadap Pemahaman Bacaan Siswa SMP di Bali - Veronica Kristiyani; Sri Hartati R Suradijono (Fakultas Psikologi Universitas Tarumanagara, 2020)
The research examined the contribution of parental beliefs and students’ self-regulated learning simultaneously toward students’ reading comprehension of junior high school in Bali. The separate examination has also been carried out namely the contribution of Balinese parental beliefs on students' reading comprehension and the contribution of students’ self-regulated learning on reading comprehension. The sample of this research consisted of 71 junior high school students and Balinese parents living in Kabupaten Karangasem, Bali. This research sample was obtained using the nonprobability sampling method through convenience sampling technique. The research used questionnaires taken from Reading Comprehension Measuring Tools in order to measure students' reading comprehension, The Parental Beliefs Questionnaire to measure parents' beliefs and Motivated Strategies for Learning. The research data were analyzed using multiple regression analysis and simple regression analysis conducted using SPSS 23 and qualitative analysis. The results showed that parental beliefs and students' self-regulated learning simultaneously influenced students’ reading comprehension in Bali. Students’ self-regulated learning also had a significantly positive effect on reading comprehension. However, Balinese’s parental beliefs did not directly contribute to reading comprehension.